Virtual Heritage: Preserving Acehnese Culture through Interactive Roblox Experiences - Giawa, Fajri; Bahruni, Bahruni; Al-Bahri, Fauzan Putraga (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
This research crafts and tests a Roblox-based Acehnese cultural learning environment showcasing virtual tours of key heritage landmarks, including the Baiturrahman Grand Mosque, traditional Rumoh Aceh houses, and coastal ecological zones. Following a Research and Development approach with two-phase testing, the platform weaves together folklore-driven quests, dance reconstruction challenges, artifact recognition activities, and team-based puzzles. Findings reveal strong quest completion rates (85%) alongside marked improvements in cultural knowledge (from 32% to 76%) among the 100 teenage participants. The multiplayer design fostered genuine social connections, averaging 3.2 group problem-solving moments per session, while nearly two-thirds of players expressed desire to visit the actual locations. The adaptive difficulty system kept challenges engaging without overwhelming players. The project demonstrates how thoughtfully designed virtual environments serve as living cultural spaces where heritage breathes through active participation rather than passive observation, building bridges across generations and geography.